Characterization of pH dependent Mn(II) oxidation strategies and formation of a bixbyite-like phase by Mesorhizobium australicum T-G1 - Bohu, Tsing; Santelli, Cara M.; Akob, Denise M.; Neu, Thomas R.; Ciobota, Valerian; Rösch, Petra; Popp, Jürgen; Nietzsche, Sándor; Küsel, Kirsten (Frontiers in Microbiology, 2015)
Despite the ubiquity of Mn oxides in natural environments, there are only a few observations of biological Mn(II) oxidation at pH < 6. The lack of low pH Mn-oxidizing bacteria (MOB) isolates limits our understanding of how pH influences biological Mn(II) oxidation in extreme environments. Here, we report that a novel MOB isolate, Mesorhizobium australicum strain T-G1, isolated from an acidic and metalliferous uranium mining area, can oxidize Mn(II) at both acidic and neutral pH using different enzymatic pathways. X-ray diffraction, Raman spectroscopy, and scanning electron microscopy with energy dispersive X-ray spectroscopy revealed that T-G1 initiated bixbyite-like Mn oxide formation at pH 5.5 which coincided with multi-copper oxidase expression from early exponential phase to late stationary phase. In contrast, reactive oxygen species (ROS), particularly superoxide, appeared to be more important for T-G1 mediated Mn(II) oxidation at neutral pH. ROS was produced in parallel with the occurrence of Mn(II) oxidation at pH 7.2 from early stationary phase. Solid phase Mn oxides did not precipitate, which is consistent with the presence of a high amount of H2O2 and lower activity of catalase in the liquid culture at pH 7.2. Our results show that M. australicum T-G1, an acid tolerant MOB, can initiate Mn(II) oxidation by varying its oxidation mechanisms depending on the pH and may play an important role in low pH manganese biogeochemical cycling.